Qualitative Responses/Recovery in Repressive Times. Issue 2 (August 2021) - Alexander, Bryant Keith; Douglas, Kitrina
The Special Section documents the resonance of the cancelation of ICQI 2020 in three movements. First, the coming together of long-time participants through electronic means for a short performative video that featured collaborative voices speaking to the power and importance of critical qualitative research in repressive times. Second, documenting on May 21, 2020, on what would have been the first day of the conference, a Zoom gathering was held with nearly 30 scholars from around the world, who would have converged on the University of Illinois-Urbana campus–responding together in a virtual but all-together real community space to share thoughts, feelings, outpourings, promises, and possibilities of critical qualitative research in repressive times. Third, a short sampling of performative scholarships reflecting on both themes of anticipated ICQI panels and emergent commentaries on world politics, COVID-19, the environment, revolution, resistance, and hope.